European Honey Bee Apis mellifera Linnaeus and subspecies (Insecta: Hymenoptera: Apidae) - Ashley N. Mortensen; Daniel Schmehl; Jamie Ellis (EDIS)
This document provides an overview of the European honey bee, Apis mellifera, detailing its natural distribution, subspecies, and introduction to the Americas. It covers the biology, life cycle, and social structure of honey bee colonies, emphasizing the roles of workers, drones, and queens. The article also discusses the economic importance of honey bees in pollination and honey production, as well as management practices and challenges, including pests and diseases. The information is intended for both laypersons with some biological knowledge and academic audiences.